DIFFRACTION IMAGE OF PRIMARY NARROW X-RAY BEAM IN WEAKLY DEFORMED CRYSTAL - Grigoryan, G.R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2012)
Huygens–Fresnel principle for dynamical diffraction of X-rays in a crystal with weak deformation field of its space lattice is stated with a view to construction of the wave functions of diffracted beams in the crystal lattice at an arbitrary distance r of the point source of primary radiation from the crystal. In particular, the well-known approximations of an incident spherical (r = 0) and plane (r→∞) waves result as the limiting cases of the problem under consideration. Some features of the interference absorption (the Borrmann effect) of X-ray wave packages in a crystal with weak field of lattice displacements were discussed.